The spectral evolution of the first galaxies: III. Simulated James Webb space telescope spectra of reionization-epoch galaxies with Lyman continuum leakage - Zackrisson, Erik; Paardekooper, Jan-Pieter (Arxiv, 2017)
Using four different suites of cosmological simulations, we generate synthetic spectra for galaxies with different Lyman continuum escape fractions (fesc) at redshifts z=7-9, in the rest-frame wavelength range relevant for the James Webb Space Telescope (JWST) NIRSpec instrument. By investigating the effects of realistic star formation histories and metallicity distributions on the EW(Hb)-beta diagram (previously proposed as a tool for identifying galaxies with very high fesc), we find that neither of these effects are likely to jeopardize the identification of galaxies with extreme Lyman continuum leakage. Based on our models, we expect essentially all z=7-9 galaxies that exhibit rest-frame EW(Hb)< 30 Å to have fesc>0.5. Incorrect assumptions concerning the ionizing fluxes of stellar populations or the dust properties of z>6 galaxies can in principle bias the selection, but substantial model deficiencies of this type will at the same time reveal themselves as an offset between the observed and simulated distribution of z>6 galaxies in the EW(Hb)-beta diagram. Such offsets would thereby allow JWST/NIRSpec measurements of these observables to serve as input for further model refinement.
Gesehen am 26.10.2017